O USO DA AÇÃO DIRETA DE INCONSTITUCIONALIDADE COMO PROLONGAMENTO DA DISPUTA POLÍTICA - Robl Filho, Ilton Norberto; Souza Neto, Cláudio Pereira de; Cunha, João Paulo (Revista da AJURIS - Qualis A2, 2023)
THE USE OF DIRECT UNCONSTITUTIONALITY ACTION AS AN EXTENSION OF POLITICAL DISPUTE ÁREA(S): direito constitucional; processo constitucional. RESUMO: Trata-se de trabalho em que, a partir de uma observação empírica do manejo de ação direta de inconstitucionalidade (ADI), no controle concentrado, exercido pelo legitimado partido político em face de leis federais aprovadas pelo Parlamento brasileiro ou submetido ao seu crivo, percebeu-se a repetição dos mesmos argumentos esgrimidos na disputa interna do Poder Legislativo ser arrastada para a tribuna do Supremo Tribunal Federal (STF). Secundou essa observação a localização dos partidos no xadrez político, ou seja, estando na oposição, o partido político opera mais com essa ferramenta (ADI), enquanto, na situação, dispensa-a. Sobreleva, por outro lado, o conteúdo das ações perante a Corte: invariavelmente são assuntos mais afeitos à Administração Púbica federal e menos à defesa dos direitos fundamentais. Assim, o trabalho problematiza, como tantos outros estudiosos já o fizeram, a relação dos assuntos levantados e sua interface com a democracia. ABSTRACT: This thesis is based on an empirical observation of the handling of Direct Actions of Unconstitutionality (ADI in Portuguese) in centralized judicial review cases; when legitimately exercised by a political party, against federal laws approved by the Brazilian Parliament or submitted to its scrutiny. A repetition of the arguments used in the internal disputes of the Legislative Power has been perceived and dragged out to the Supreme Federal Court (STF in Portuguese). Seconding this observation, was the position of the parties on the political chessboard, that being – pertaining to opposition parties; they tend to use this tool more frequently, while in the situation it contradicts their interests; they try to avoid it. Nevertheless, the content of the actions that prevail before the Court are; inevitably, matters closely related to the public federal administration, rather than aimed at the defense of fundamental rights. Thus, the present work studies; as many other scholars have done beforehand, the relation between the issues raised and their effects on democracy. PALAVRAS-CHAVE: constitucionalismo; controle concentrado; judicialização da política; democracia; ação direta de inconstitucionalidade; Poder Legislativo; Supremo Tribunal Federal. KEYWORDS: constitutionalism; concentrated control; judicialization of politics; democracy; direct unconstitutionality action; Legislative Power; Federal Court of Justice. SUMÁRIO: Introdução; 1 Constituição, controle de constitucionalidade e democracia; 2 Os partidos políticos e a ação direta de inconstitucionalidade; 3 A separação dos poderes; 4 Poder Legislativo: entre a democracia e o judicial review; 5 Ação direta de inconstitucionalidade: propostas levadas ao STF pelos partidos políticos; 6 Medidas provisórias e ação direta de inconstitucionalidade; Conclusão; Referências. SUMMARY: Introduction; 1 Constitution, judicial review and democracy; 2 Political parties and the direct action of unconstitutionality; 3 Separation of powers; 4 Legislative Power: between democracy and judicial review; 5 Direct action of unconstitutionality: proposals taken to the STF by political parties; 6 Provisional measures and the direct action of unconstitutionality; Conclusion; References.